Problematika dalam Perkawinan - Hidayani Syam; Wapiq Azzahra; Ari Nasowaloon Harahap (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Marriage is a social institution that plays an important role in people's lives. Through marriage, two individuals form a family that is expected to be a place of affection, emotional support, and social stability. However, in practice, not all marriages run harmoniously. Various problems often arise, both originating from within the couple, differences in cultural background, economy, or the influence of the surrounding environment. Problems in marriage can include communication conflicts, incompatibility of values ​​and life principles, economic problems, and even infidelity. Not infrequently, pressure from the extended family and changes in gender roles also complicate household dynamics. If not handled properly, these problems can lead to disharmony, even divorce.